Chinese Patent Medicine Tongxinluo Capsule for Hypertension: A Systematic Review of Randomised Controlled Trials. (17th February 2014) - Wang, Jie; Xiong, Xingjiang; Liu, Wei
Abstract : Background . This study was intended to evaluate the efficacy and safety of Tongxinluo capsule for hypertension. Search Strategy . We searched the Cochrane Central Register of Controlled Trials (CENTRAL) in the Cochrane Library, The PubMed, EMBASE, Chinese Bio-Medical Literature Database (CBM), Chinese National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database, and Wan-fang Data started from the first of database to October 28, 2013. No language restriction was applied. We included randomized clinical trials testing Tongxinluo capsule against western medicine, Tongxinluo capsule versus placebo, and Tongxinluo capsule combined with western medicine versus western medicine. Study selection, data extraction, quality assessment, and data analyses were conducted according to the Cochrane standards. Results . 25 trials with 1958 participants were included. The methodological quality of the included trials was evaluated as generally low. The blood pressure (BP) lowering effect of Tongxinluo capsule plus western medicine was significantly higher than that of western medicine (systolic blood pressure (SBP): −3.87, −5.32 to −2.41, P < 0.000 0 1 ; and diastolic blood pressure (DBP): −2.72, −4.19 to −1.24, P = 0.0003 ). The BP also decreased significantly from baseline with Tongxinluo capsule than placebo (SBP: −9.40, −10.90 to −7.90, P < 0.000 0 1 ; and DBP: −11.80, −12.40 to −11.20, P < 0.000 0 1 ) or western medicine (SBP: −3.90, −4.93 to −2.87, P < 0.000 0 1 ; and DBP: −3.70, −3.83 to −3.57, P < 0.000 0 1 ). 12 trials reported adverse events without details. Conclusions . There is some but weak evidence about the effectiveness of TXL in treating patients with hypertension.